Sosialisasi Penerapan Sistem Informasi Pendidikan untuk Pengelolaan Data Guru dan Akademik Berbasis Web - Akhmad Sayuti; Irwansyah Irwansyah; Tri Akhyari Romadhon; Amelia Anggraini; Rahmi Rahmi (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
Science nowadays is developing very rapidly. The increasing need for information encourages humans to develop new technologies so that data and information processing can be done easily and quickly. To make everything easier, of course we don't just use human power, but use modern technology, for example by utilizing internet technology. The existence of technology, especially Web-Based Information Systems, is interpreted as an effort to increase effectiveness and efficiency and is developed to solve problems faced by admins and teachers, especially in managing school academic data. Bina Sriwijaya Indonesia Palembang Vocational High School (SMK) is a School/Educational Institution under the auspices of the Bina Sriwijaya Foundation which has 4 majors as follows, Office Administration, Computer Accounting, Computer Network Engineering, Hospitality Accommodation currently does not utilize Web-Based Information System technology. As a result of this, it is difficult for the school to increase the productivity of school services ranging from information facilities to academic data processing which are less effective and efficient. By looking at these problems, it is necessary to hold outreach for admins and teachers to manage school academic data by utilizing the Web-Based Information System at the Bina Sriwijaya Vocational High School (SMK).